Preparation of extracted magnetite from an industrial waste mill modified by cetyl trimethyl ammonium bromide for cadmium ion removal from aqueous solution - Ahmad Nazri, Nur Asyikin; Azis, Raba’ah Syahidah; Che Man, Hasfalina; Ismail, Ismayadi (Malaysian Analytical Sciences Society, 2022)
This work, using a batch study, revealed the performance of modified magnetite millscales with a cationic surfactant [cetyl trimethyl ammonium bromide (CTAB)] (Fe3O4/CTAB MNS) in cadmium ion removal from aqueous solution. The self-assembly method was employed to modify Fe3O4 with CTAB. As prepared Fe3O4 limited the modification method to ex situ. Therefore, a heterocoagulation method was used to self-assemble CTAB on Fe3O4. The prepared magnetic nanosorbents (MNSs) were used in batch adsorption to optimize cadmium adsorption. In addition, characterization with Fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM) revealed new characteristics of that modified Fe3O4 that contributed to the enhancement of the adsorption efficiency (Q) to reach 21.6 mg/g. The higher removal percentage shown by Fe3O4/CTAB MNS was 89%, which confirmed the successful modification. Therefore, Fe3O4 modified with CTAB has higher potential to be used as magnetic nanosorbent owing to lower cost of production with compatible adsorption capacity.